2009
DOI: 10.1080/15332840903323364
|View full text |Cite
|
Sign up to set email alerts
|

Role Stress, Emotional Exhaustion, and Turnover Intentions: Does Organizational Tenure in Hotels Matter?

Abstract: The purpose of the present study was to investigate organizational tenure as a moderator of the relationships between role stress (role conflict and role ambiguity) and emotional exhaustion and turnover intentions. Data were gathered from a sample of full-time frontline hotel employees in Northern Cyprus to test the previously mentioned relationships. Results of hierarchical moderated regression analysis demonstrated that the positive effects of role conflict and emotional exhaustion on turnover intentions wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 37 publications
2
60
0
Order By: Relevance
“…The study findings confirmed and extended upon the findings of previous studies in hospitality settings (Babakus et al, 2008;Jung et al, 2012;Karatepe & Karatepe, 2010). Of the three role stress factors, RO had a strong and positive effect on EE, whereas RA had the weakest effect.…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…The study findings confirmed and extended upon the findings of previous studies in hospitality settings (Babakus et al, 2008;Jung et al, 2012;Karatepe & Karatepe, 2010). Of the three role stress factors, RO had a strong and positive effect on EE, whereas RA had the weakest effect.…”
Section: Resultssupporting
confidence: 94%
“…Chen et al's study (2011) confirmed the role stressors (RA, RC, and RO). In terms of hospitality settings, previous studies have mixed results regarding the effect of role stressors on EE and turnover intention (Babakus et al, 2008;Chen et al, 2011;Jung et al, 2012;Karatepe & Karatepe, 2010). Furthermore, no known studies utilized all three role stressors to test their effect on EE.…”
Section: Role Stress Research In Hospitality Settingsmentioning
confidence: 90%
See 2 more Smart Citations
“…There has also been research (Karatepe and Karatepe, 2009;Ross and Boles, 1994) showing that employees in hotel businesses are confronted with role stress. For this reason, within the scope of this research, it has been decided that role stress, as a source of job stress, should be scrutinized.…”
mentioning
confidence: 99%